Estudio de la producción beneficiado y comercialización de cacao para las zonas de Mirador San Jacinto y Guadalupe - Cruz Ibáñez, Mauricio Efraín (2006)
The present work will comprise of the "definitive Studies of Subproyecto benefitted Intercantonal of production and commercialization of cacao in the low zones of Pucará, Ponce Enríquez and Pijilí", propose that is being developed in Agreement with the M. I. Municipalidad of Ponce Enríquez, the University of Machala through the Department of Entailment with the Community of the Faculty of Farming Sciences and the Foundation Progress and Development PRODE, the project is financed by PROLOCAL and will be presented/displayed to the Inter-American Development Bank I.A.D.B.. }he surveys were made in the cacaoteras property of the communities of Viewpoint, San Jacinto and Guadalupe sectors pertaining to the Camilo Corner Ponce Enríquez of the Province of the Azuay, the objectives that considered were: OBJECTIVES: 1. To diagnose of integral way the productive and commercial supply of the culture. 2. To establish one structures organizacional and beneficiary in the zone in study.As result of the integral diagnosis of the productive and commercial supply we have the good productivity of the Sector of Viewpoint with 8,14 qq/ha (fresh dry +), the Guadalupe Zone with an average of 5,70 production of qq /ha/año and San Jacinto with 4.52 qq /ha/año; against 8,2 qq/promedio/país and 10 qq average in the zone of Orange grove, the goal to both years of intervention of the project will obtain to a 9 production of qq /ha/año in the Sector Viewpoint, 7 qq/ha/año in the sector of Guadalupe and 6 qq/ha/año in San Jacinto, average that will be competitive for the cacaoteros producers.In order to obtain this 35% of increase in the production a qualification process will be necessary, technical attendance and permanent support to the cacaoteros.Of equal way a -35% of weaknesses in the aspect organizacional partner exists, for which has planned the fortification of the capacities of the agriculturist and the necessity to form an organizational structure of the second degree, with legal life approved by the organizations involved in the project.The proposal of intervention he is planned for two years through an intensive process of qualification and technical attendance, which will allow to improve the levels of production and commercialization. In order to implement the proposal of direct commercialization, eliminating the intermediaries who absorb a great margin of utility without making no type of investment, a center of storing located in Shumiral will be implemented sector bordering to the zones in study.